Preservice Science Teachers’ Performance Expectancy of E-Assessment in Colleges Of Education - Adeyanju Lawrence Olugbade (IJER (Indonesian Journal of Educational Research), 2022)
E-examination has been seen as an alternative to the unmanageable population of pre-service science teachers. This study was conducted to investigate the pre-service science teacher’s perception of e-examination for examining science related courses. To this end it examined the potentials for using pre-service science teacher’s feedback in the validation of assessment. A convenient sample of 120 pre-service sciences teachers from four cohorts in the school of science was selected from the college of education. Descriptive research of the survey type was used. Questionnaires which were tested for reliability using Cronbach alpha which stood at 0.910 were used as data collection instruments. Descriptive statistics of the frequency count and percentages were used to answer the four research questions raised. The major findings from the analysis revealed that high percentage of pre-service science teachers perceives e-examination to be necessity in the production of outstanding science teachers from tertiary institutions. Based on these results, it is recommended that the government should adopt the use of e-examination for evaluation in tertiary institutions in Nigeria and lectures should involve more technologies